Cerebral Cortical Aβ42 and PHF-τ in 325 Consecutive Brain Autopsies Stratified by Diagnosis, Location, and APOE. Issue 2 (February 2015) - Postupna, Nadia; Keene, Christopher Dirk; Crane, Paul K.; Gonzalez-Cuyar, Luis F.; Sonnen, Joshua A.; Hewitt, Jessica; Rice, Samantha; Howard, Kimberly; Montine, Kathleen S.; Larson, Eric B.; Montine, Thomas J.
<x xml:space="preserve">Abstract</x> Abstract We used a novel approach to molecular quantification in standard fixed and embedded tissue to measure amyloid β 42 (Aβ42) and paired helical filament-τ (PHF-τ) in frontal, temporal, and parietal cortices from 325 consecutive brain autopsies collected as part of a population-based study of brain aging and incident dementia in the Seattle area. We observed significant effects of APOE ε4 on Aβ42 levels in both diagnostic groups by disease stage and region. In contrast, we did not observe a significant effect of APOE ε4 on PHF-τ levels by disease stage in any region. Levels of Aβ42 and PHF-τ in cerebral cortex were correlated more strongly in the Dementia group, and these measures had independent explanatory power for dementia beyond those of standard neuropathologic indices. Associations between Lewy body disease and Aβ42 or PHF-τ levels and between Aβ42 levels and microvascular brain injury suggested that these comorbid diseases enhanced the penetrance of Alzheimer disease. Our novel approach brings additional insights into the molecular pathogenesis of common causes of dementia and may serve as a platform for future studies pursuing associations between molecular changes in Alzheimer disease and genetic or environmental risk.